Arsenic Biomonitoring in the Human Population of Yellowknife, Dettah and Ndilo, Northwest Territories: Application of Urine and Toenail Arsenic Biomarkers - Cheung, Janet (Université d'Ottawa / University of Ottawa, 2023)
Arsenic is a natural but toxic element considered by the World Health Organization to be a chemical of major public health concern globally. Biomarkers are a tool used to understand exposure to chemicals (e.g., arsenic) and their impacts on the health of a population. In Yellowknife, past mining activities have resulted in a toxic legacy of arsenic impacting the surrounding environment. However, current human exposure levels in the area are largely unknown. In this thesis, I demonstrate how different biomarkers can be used to evaluate arsenic exposure and associated health effects in the human population of Yellowknife and the First Nation communities of Dettah and Ndilo. First, I established baseline levels of arsenic exposure within the Yellowknife population by measuring urinary arsenic concentrations via speciation analysis. I also used general guidance values for urinary arsenic to assess arsenic exposure and health risks in Yellowknife compared to the general Canadian population. Children in Yellowknife had significantly higher urinary inorganic arsenic concentrations than Yellowknife adults and children in the general Canadian population. Second, I expanded on the baseline arsenic exposure levels by analyzing toenail arsenic via speciation analysis, demonstrating that toenail arsenic reflects a different exposure period than urine and may potentially indicate external environmental sources. Then, I evaluated two proteins, KIM-1 and CC16, as candidate biomarkers of effect for detecting lung and kidney impairment in children from exposure to arsenic and other contaminants (e.g., lead and manganese). Finally, I reviewed past archival human arsenic data to understand historical arsenic exposure and how past exposures compare to current levels. I have demonstrated that different biomarkers can contribute to understanding arsenic exposure and its subsequent impacts on the Yellowknife population and other populations with similar environmental health concerns. Additionally, the results of my research contribute to public health policy and decision-making.
Keywords: arsenic; human biomonitoring; biomarkers; environmental health; environmental toxicology